The role of loco-regional treatment in long-term quality of life in de novo stage IV breast cancer patients: protocol MF07-01Q - GÜLLÜOĞLU, MAHMUT BAHADIR; UĞURLU, MUSTAFA ÜMİT (SPRINGER, 2021)
Background/objective Since more solid evidence has emerged supporting the effectiveness of loco-regional treatment (LRT), clinicians consider LRT a treatment option for selected de novo stage IV breast cancer (BC) patients. This is the first report on long-term quality of life (QoL) in a cohort of patients who were randomized to receive either LRT and then systemic treatment (ST) or ST alone in the protocol MF07-01. We aimed to evaluate QoL in patients living at least 3 years since randomization using scores from the SF-12 health survey. Methods SF-12 (V2) forms were completed during visits of patients who were living 36 months after the randomization. We first calculated PCS-12 (Physical Health Composite Scale) and MCS-12 (Mental Health Composite Scale) scores from de novo stage IV BC patients and compared them with the scores of patients diagnosed with stage I-III BC who lived more than 3 years. Further, PCS-12 and MCS-12 scores were compared between the LRT and ST groups with de novo stage IV BC. Additionally, general health, physical functioning, role functioning, bodily pain, vitality, mental health, and social functioning were evaluated and compared between the groups. Considering age-related changes in QoL, we also compared PCS-12 and MCS-12 scores of patients below or above 55 and 65 years of age. Responses to four additional questions (compare your physical health, mental health, daily activities, and energy currently vs. at diagnosis of BC) were recorded, considering cultural differences. Results There were 81 patients in this analysis; 68% of patients (n = 55) had LRT, and 32% (n = 26) received ST. General health was good or very good in 62% (n = 34) in the LRT group and 66% (n = 17) in the ST-only group (p = 0.63). Mean PCS-12 score was 40.8 + 1.6, and mean MCS-12 score was 43.4 + 2.0 (p = 0.34 and p = 0.54, respectively). PCS-12 and MCS-12 score difference was lower than that of the general Turkish population (PCS-12 = 49.3 + 12.8 and MCS-12 = 46.8 + 13.0) and stage I-III BC patients (PCS-12 = 51.1 +/- 0.5, MCS-12 = 45.7 +/- 0.6). PCS-12 and MCS-12 scores were similar between the LRT and ST-only groups in patients younger and older than 55 and 65, but QoL scores were much better in stage I-III BC patients younger than 65 when compared to the scores of those with de novo stage IV BC. Although treatment with or without LRT did not affect physical health, mental health, daily activities, and energy at 3 years vs. at diagnosis of BC in de novo stage IV BC patients (p > 0.05), these variables were significantly better in stage I-III BC patients (p < 0.001). Conclusion The current MF07-01Q study demonstrates that patient who had LRT has similar physical and mental health outcomes compared to ST only in a cohort of patients who lived longer than 3 years. Trial registration This study is registered on clinicaltrials.gov with identifier number NCT00557986.
Keywords: Breast cancer; Stage IV; De novo; Surgery; Quality of life; 20-YEAR FOLLOW-UP; PRIMARY TUMOR; SURGICAL RESECTION; SYMPTOM BURDEN; CONSERVING THERAPY; MASTECTOMY; SURVIVAL; SURGERY; IMPACT; WOMEN